The facilitating effect of unfavorable lactation on the potentiation of electrocorticogram after spreading depression in awake and anesthetized adult rats. - Marinho de Souza, Thays Kallyne; e Silva-Gondim, Mariana Barros; Rodrigues, Marcelo Cairrão Araújo; Guedes, Rubem Carlos Araújo (Nutritional Neuroscience, 2018)
Objectives: Cortical spreading depression (CSD) is a brain excitability-related phenomenon that can be affected by unfavorable conditions of lactation and by anesthetic agents. We have previously demonstrated that after CSD the electrocorticogram (ECoG) amplitude increases significantly (ECoG potentiation). Here, we investigated this potentiation in awake and anesthetized adult rats that were previously suckled among different lactation conditions. Methods: Newborn rats were suckled in litters with 6 pups or 12 pups (L6 or L12 condition, respectively). At adulthood, we evaluated the ECoG potentiation after CSD at two cortical points (one point near, and another remote to the CSD-eliciting site). The amplitude of the ECoG waves was averaged with the support of an algorithm implemented in Matlab™ software. In both L6 and L12 condition, awake animals were compared with anesthetized groups that received either tribromoethanol- or urethane + chloralose-anesthesia. Results: L12 rats presented significantly lower body- and brain weights than L6 rats (P < 0.01), indicating a nutritional deficiency. The anesthetized L6 groups presented with ECoG potentiation (P < 0.05) only in the near cortical recording point (28.0% and 32.6% increase for the tribromoethanol and urethane + chloralose groups, respectively), whereas the L12 groups displayed ECoG potentiation in both near (67.0% and 55.0%) and remote points (37.0% and 20.0%), in comparison with the baseline values (before CSD). Discussion: The results suggest a facilitating effect of unfavorable lactation on the potentiation of ECoG after spreading depression in anesthetized adult rats. The potential implications for the human neurological health remain to be investigated.